Carried Out By Deeds Under Hand Is Reviewed From The Civil Code And The Compilation Of Islamic Law - Sunardi, Sunardi; Dewi Navisa, Fitria; Hasbullah, Hasbullah (International Significance of Notary, 2025)
Abstract: In the law, lands that do not have a certificate cannot be said to be the property of the person who owns them. This is because the land does not have a valid certificate. Even if the land is obtained from inheritance, sale, grant, will or because of the customs of the local community, because if there is no strong evidence, then the land is not fully owned by the person who owns it. As for the formulation of the first issue raised, how is the legal force of grant land that is not carried out by a notary deed reviewed from the Civil Code and the Compilation of Islamic Law? Second, how is the settlement of land grants that are not carried out by a notary deed reviewed from the Civil Code and the Compilation of Islamic Law? This type of research is a normative study using a legal, constitutional approach and case studies that focus on grant dispute land that is not carried out by a notary deed. This research is descriptive in nature which aims to present clear and systematic details of the main problem. The legal force of the deed of grant of immovable objects, namely land, lies in the function of the authentic deed itself, namely as a valid evidence according to the law (Articles 1682, 1867 and 1868 of the Civil Code), that there must be authentic deeds as a means of proof. In order to be a valid evidence, the grant deed must be made and signed by the authorized official as well as the party bound to it. Meanwhile, according to Islamic law, an agreement under hand is a valid thing, but such an agreement cannot be a strong evidence. The basic similarity, both the civil code and the compilation of Islamic law, are equally valid that distinguishes them, namely in the power of law and proof. In resolving land disputes, both according to the civil code and the compilation of Islamic law can be done in various ways. Among other things, through the courts, complaints to the land office and peacefully through mediation. First, peaceful dispute resolution through mediation. As an alternative to land dispute resolution, mediation is a priority outside the court in order to reach consensus, a short dispute resolution time, a structured, task-oriented, and active participation.